Cameroon : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1999)
This Selected Issues paper and Statistical Appendix highlights that after eight years of decline, economic activity of Cameroon began to pick up following the January 1994 devaluation of the CFA franc, the accompanying upturn in world economic activity, and favorable international commodity prices. Real GDP, which had fallen by an annual average of 4 percent since the mid-1980s, began to recover, with the annual growth rate stabilizing at about 5 percent in the three years to 1997/98. In the policy area, the 1994 devaluation was accompanied by tax and trade reforms.